Surgical morbidity of laparoscopic hysterectomy versus abdominal hysterectomy: A retrospective overview - Mukta Agarwal; Shivangni Sinha; Smita Singh; H Haripriya; Ishita Roy (Wolters Kluwer Medknow Publications, 2023)
Objectives: Laparoscopic skills are not an innate behavior, nor can they be easily mimicked, and can only be acquired through hands-on training. The need for reliable training and its assessment is becoming increasingly important with the course of time. Materials and Methods: A retrospective comparative study was done in a tertiary care center where all patients undergoing hysterectomy by laparoscopic and abdominal route were included in the study. Objectives: Our study aims to compare the operative and postoperative complications of laparoscopic hysterectomy with abdominal hysterectomy. The study was conducted from June 2016 to October 2022. Results: The mean operative time for uteri size lesser than 12 weeks was found significant in the total laparoscopic hysterectomy (TLH) group (75 ± 25 min) to total abdominal hysterectomy (TAH) (117 ± 28 min, P < 0.001). The mean blood loss in the TLH group was significant (110 ± 30 ml vs. 160 ± 116 ml, P < 0.002). The mean hospital stay was significantly shorter in TLH (4 ± 2.4 days vs. 7 ± 2.41 days, P < 0.002). The operative and postoperative complications observed were 3.1% in the TLH group and 11.7% in the TAH group. Conclusion: TLH when performed efficiently has proved to be a preferable route over other conventional hysterectomies.